2003
DOI: 10.4141/a03-021
|View full text |Cite
|
Sign up to set email alerts
|

Amino acid requirements in inflammatory states

Abstract: Obled, C. 2003. Amino acid requirements in inflammatory states. Can. J. Anim. Sci. 83: 365-373. The metabolic disturbances that accompany an inflammatory challenge redirect nutrients from physiological processes important for growth and reproduction toward processes important in host defense. These processes can require increased provision of particular amino acids from the diet in order to spare body protein stores. The pathways that are activated in response to inflammation have to be determined in order to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 85 publications
(48 reference statements)
0
30
0
Order By: Relevance
“…However, during d 15 to 28 after castration the ADG of BURD castrates seemed to be recovered compared with CON. The reduction in growth may be, in part, due to the immediate tissue trauma, inflammation (Obled, 2002), and probably psychological (pain) stress in response to castration, and the loss of anabolic (testosterone) steroid ( Knight et al, 1999a and b). BURD had an advantage in ADG over BAND in the period of d 15-28 post-castration.…”
Section: Discussionmentioning
confidence: 98%
“…However, during d 15 to 28 after castration the ADG of BURD castrates seemed to be recovered compared with CON. The reduction in growth may be, in part, due to the immediate tissue trauma, inflammation (Obled, 2002), and probably psychological (pain) stress in response to castration, and the loss of anabolic (testosterone) steroid ( Knight et al, 1999a and b). BURD had an advantage in ADG over BAND in the period of d 15-28 post-castration.…”
Section: Discussionmentioning
confidence: 98%
“…Intestinal glutamine requirement has also been linked to the activation of the immune response during infection 33 . Thus, the increased uptake of glutamine by the MDV (P¼0 •14) and PDV (P, 0•05) of parasitised lambs may be due to increased requirements by the intestine for the repair of damaged tissue and local immune response.…”
Section: Discussionmentioning
confidence: 99%
“…Threonine was released from the liver of parasitised lambs compared with a net uptake for the control lambs. Threonine is an important EAA for acute-phase protein synthesis in the liver during immune responses 33 and for intestinal secretions 34 -36 . The reason for increased hepatic utilisation of only the BCAA in the parasitised lambs is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, sick animals are often in anorexic state and have to rely on mobilization of body reserves to meet their nutritional needs. Skeletal muscle catabolism increases free amino acids into the circulation that, in turn, can be used in the liver for the synthesis of acute phase proteins, as well as substrate for gluconeogenesis (Hasselgren and Fischer, 1999;Leverve, 2001;Obled, 2003). Accordingly, Daiwen et al (2008) observed lower protein retention in pigs challenged intramuscularly with LPS when compared with their pair-fed counterparts receiving a saline solution.…”
Section: Metabolic Adjustmentsmentioning
confidence: 94%